Climate change and its effects on biodiversity conservation and gastronomy - Victor Pulido-Capurro (2025)
Climate change is one of the main concerns facing the human species in the present circumstances. The resulting effects are many in economic, social and environmental terms. In this article we refer to the implications of biodiversity conservation in Peru and its close relationship with gastronomy, one of the country’s main economic activities and a fundamental pillar in the recognition and preservation of our cultural identity. The objective is to analyze the effects of climate change on biodiversity and its impact on Peruvian gastronomy. The research is qualitative and descriptive, based on three thematic axes. It is concluded that climate change is generating significant effects on the conservation of biodiversity, altering the distribution limits of populations and modifying population patterns, which puts the survival of many species at risk. It also highlights that biodiversity is the fundamental axis of inputs that supply Peruvian cuisine, so that conservation efforts will contribute directly to the sustainability of the country’s gastronomy.